Perempuan dalam Pembangunan dan Politik: Perspektif Sosial Budaya Manggarai - Girwan, Alfianus Fridolin; Noak, Piers Andreas; Erviantono, Tedi (Jurnal Nawala Politika, 2023)
Gender has an important position in achieving sustainable development goals. Social construction that places gender as one of the differentiating criteria in the community’s socio-cultural, it makes women have limited space as part of a marginal group in society. The role of women in development aspects, such as in politics is increasingly open. However, women's involvement in the public is always faced with various obstacles. This study aims to examine the socio-cultural perspectives of the East Manggarai community regarding the position of women in development and politics. This research is using qualitative method, with data collection techniques through interviews and literature studies. The results of the study show that the role of women in politics and development in East Manggarai is still low. Patriarchal culture also influences the social perspective of the Manggarai people about women in politics. Furthermore, women's involvement in development and politics is strongly influenced by the level of education, socio-cultural perspective, political awareness, and the local environment. However, the study also shows the people of Manggarai have an awareness of the important role of women in politics and development.